Behavioural responses and anxiety symptoms during the coronavirus disease 2019 (COVID-19) pandemic in Japan: A large scale cross-sectional study. (April 2021) - Cai, Guoxi; Lin, Yulan; Lu, Yixiao; He, Fei; Morita, Kouichi; Yamamoto, Taro; Aoyagi, Kiyoshi; Taguri, Toshitsugu; Hu, Zhijian; Alias, Haridah; Danaee, Mahmoud; Wong, Li Ping
Abstract: Background: This study explored the behavioural responses and anxiety symptoms of the general adult population in Japan during the ongoing coronavirus disease 2019 (COVID-19) outbreak. Methods: A web-based cross-sectional survey was conducted between 12th and May 13, 2020. Quota sampling was used to attain equal gender and age distributions representative of the Japanese population. Results: A total of 4127 complete responses were analysed. Higher educational level (B = 0.045, p  = 0.002) and household income (B = 0.04, p  = 0.009) were associated with a higher increase in preventive measures when comparing before and after the state of emergency was declared. The highest reported social anxiety was a feeling of fear (65.6%), followed by embarrassment (43.8%), keeping infection a secret (41.3%), avoidance (41.3%), and stigma (25.5%). A total of 86.1% of the respondents reported moderate to severe anxiety. The partial least square-based structural equation modelling (PLS-SEM) revealed that being female has the greatest effect (B = 0.246, p  < 0.0001) on higher current preventive measures, followed by social anxiety (B = 0.119; p  = 0.001) and State-Trait Anxiety Inventory scores (B = 0.153; p  < 0.001). Perceived susceptibility (B = 0.033, p  = 0.020), knowing someone who have been diagnosed with COVID-19 (B = 0.097, p  < 0.001), higher income (B = 0.079, p  < 0.001) and educational level (B = 0.045; p  = 0.004) all had a small but significant effect on influencing levels of preventive measures. Conclusions: A moderate level of preventive practices found in this study indicates the need to encourage behavioural change to limit the spread of the coronavirus. The provision of mental health services is warranted as anxiety symptoms are prevalent.